Acute Pancreatitis and Diabetic Ketoacidosis following L-Asparaginase/Prednisone Therapy in Acute Lymphoblastic Leukemia - Dania Lizet Quintanilla-Flores; Miguel Ángel Flores-Caballero; René Rodríguez-Gutiérrez; Héctor Eloy Tamez-Pérez; José Gerardo González-González (Case Reports in Oncological Medicine)
Acute pancreatitis and diabetic ketoacidosis are unusual adverse events following chemotherapy based on L-asparaginase and prednisone as support treatment for acute lymphoblastic leukemia. We present the case of a 16-year-old Hispanic male patient, in remission induction therapy for acute lymphoblastic leukemia on treatment with mitoxantrone, vincristine, prednisone, and L-asparaginase. He was hospitalized complaining of abdominal pain, nausea, and vomiting. Hyperglycemia, acidosis, ketonuria, low bicarbonate levels, hyperamylasemia, and hyperlipasemia were documented, and the diagnosis of diabetic ketoacidosis was made. Because of uncertainty of the additional diagnosis of acute pancreatitis as the cause of abdominal pain, a contrast-enhanced computed tomography was performed resulting in a Balthazar C pancreatitis classification.